Dilation of Brain Veins and Perivascular Infiltration by Glioblastoma Cells in an In Vivo Assay of Early Tumor Angiogenesis. (8th March 2021) - D'Alessandris, Quintino Giorgio; Pacioni, Simone; Stumpo, Vittorio; Buccarelli, Mariachiara; Lauretti, Liverana; Giordano, Martina; Di Bonaventura, Rina; Martini, Maurizio; Larocca, Luigi M.; Giannetti, Stefano; Montano, Nicola; Falchetti, Maria Laura; et al.
Abstract : The cranial window (CW) technique provides a simple and low-cost method to assess tumor angiogenesis in the brain. The CW combined with histology using selective markers for tumor and endothelial cells can allow a sensitive monitoring of novel antiangiogenesis therapies in preclinical models. The CW was established in cyclosporine immunosuppressed rats that were stereotactically grafted with fluorescent U87MG glioblastoma cells. One to 3 weeks after grafting, brain vasculature was visualized in vivo and assessed by immunofluorescence microscopy using antibodies against endothelial and smooth-muscle cells and blood brain barrier. At 1-2 weeks after grafting, the CW reliably detected the hypertrophy of venous-venous anastomoses and cortical veins. These structures increased highly significantly their pregrafting diameter. Arterialized veins and hemorrhages were seen by three weeks after grafting. Immunofluorescence microscopy showed significant branching and dilation of microvessels, particularly those surrounded by tumor cells. Mechanistically, these changes lead to loss of vascular resistance, increased venous outflow, and opening of venous-venous anastomoses on the cortical surface. Data from the present study, namely, the hypertrophy of cortical venous-venous anastomoses, microvessel branching, and dilation of the microvessels surrounded by tumor cells, indicate the power of this in vivo model for the sensitive monitoring of early tumor angiogenesis.